Does measurement of yield pressure at the cardia during endoscopy provide information on the function of the lower oesophageal sphincter mechanism?. Issue 3 (March 1988) - McGouran, R C; Galloway, J M; Spence, D S; Morton, C P; Marchant, D
Abstract : We describe a technique for measuring the yield pressure at the cardia during upper gastrointestinal endoscopy. The test was applied to 47 patients with macroscopic oesophagitis and nine patients with achalasia. Controls were 123 patients from the routine endoscopy list in whom no abnormality was found and 21 healthy volunteers. Yield pressure was similar in both control groups, but was significantly higher in achalasia (p less than 0.001) and lower in oesophagitis (p less than 0.001). Yield pressures fell dramatically after pneumatic dilatation in the achalasia patients. The test was reproducible and yield pressure was not affected by age, sex, weight, or sedation. Measurement of yield pressure during endoscopy provides information which may reflect the function of the whole antireflux mechanism, and not just the lower oesophageal sphincter.